Covalent Modification of Glassy Carbon Surface Via Radical-Induced Grafting from Electrochemical Oxidation of Imine Derivatives - Zagal-Moya, J; Zagal-Moya, J; Pavez-Irrazabal, J; Pavez-Irrazabal, J; Silva-Molina, C; Silva-Molina, C; Agurto-Doren, N; Agurto-Doren, N; Olguín-Choupay, C; Olguín-Choupay, C; Jara-Reyes, G; Jara-Reyes, G; et al. (Elsevier Ltd, 2023)
The selective surface modification and functionalization methods through organic or inorganic grafting are a permanent challenge for constructing custom-made molecular interfaces with high performance as part of electroactive surfaces. We report the novel use of imine derivatives as a source of radical species for modifying a glassy carbon (GC) surface using electrochemical grafting. Based on the above work related to imine compounds, we designed and synthesized two structural isomers, ferrocenyl-nitro imine derivatives. These electroactive ferrocenyl and nitro functional groups served as redox signaling. In order to identify which part of the imine derivatives was grafted on the GC surface, they were subjected to electrolysis at a constant potential to monitor changes in its imine fragment response. Electrochemical and spectroelectrochemical results suggested that just one of two synthesized isomers (η5-C5H4-CH=N-C6H4-NO2)Fe(η5-C5H5) produced a radical species by electrochemical oxidation of the imine with bond cleavage. After the electrolysis process, the cyclic voltammetry and spectroscopic studies showed that a covalent modification of GC surfaces took place via forming a new bond from a nitro-aryl species on the GC surface. Due to imine bond cleavage, the ferrocenyl scissioned fragment was lost far from the electrode surface. © 2023 Elsevier Ltd